(untitled) (Indonesian Journal of Civil Engineering Study, 2024)
Seismic-resistant buildings are crucial for Indonesian society due to the high seismic risk in the area. The planning of this market building is located on Kampung Slekos street, Bandarharjo Village, North Semarang District, Semarang City, near the historic Menara Syahbandar building, on soft ground conditions. The focus of this planning is on designing a market building that can withstand earthquakes with the existing soil conditions, and it involves analyzing the forces using the Indonesian Concrete Building Code (SNI) for reinforced concrete buildings and seismic resilience standards. The method in planning the Syahbandar market building involves determining the layout and roof configuration, as well as its structural system. The planning includes using concrete roofs and reinforced concrete structural systems. Afterward, the dimensions of the structural elements are estimated using reinforcement steel with fy 420 MPa and 280 MPa, with concrete strength of K-300 for beams, columns, slabs, tie beams, and K-350 for foundations. The next step is determining the loads acting on the structure, including dead loads, live loads, and especially seismic loads.Following the estimation of structural elements and loads, the next step involves calculating the reinforcement steel to be used in each part of the structure and analyzing the response spectrum output using equivalent static analysis. The results of the calculations show that the roof and floor slabs have a thickness of 12 cm, main beams measuring 35 x 65 cm, secondary beams measuring 32.5 x 40 cm, columns measuring 40 x 40 cm on the 5th floor, 50 x 50 cm on the 3rd and 4th floors, and 60 x 60 cm on the 1st and 2nd floors. Pile cap and spun pile foundations are deemed safe and meet the criteria for concrete design and seismic resilience standards.